Investigation of IGF2, IGFBP2 and p63 proteins in rhabdomyosarcoma tumors. (April 2017) - Yu, Yongbo; Fu, Libing; Wang, Shen; Jin, Yaqiong; Han, Shujing; Chu, Ping; Lu, Jie; Guo, Yongli; He, Lejian; Ni, Xin
Abstract: Many efforts have been made to address involvement of the insulin-like growth-factor (IGF) pathway in rhabdomyosarcoma (RMS) pathogenesis, but the actual role of IGF in RMS is still controversial. Objective: To investigate the implications of IGF2, IGFBP2 and p63 in RMS, and further explored their potential interaction. Design: A total of 114 specimens of RMS along with clinic-pathologic characteristics were collected from the year of 2003 to 2013. Protein abundance was detected by immunohistochemical staining, potential relationships between protein levels and clinic-pathological parameters were applied using correlation analysis. Results: The results showed positive correlation between IGFBP2 and p63 (r = 0.271, p = 0.003), suggesting that the interaction of IGFBP2 and p63 might account for the pathogenesis of RMS. In the subtype analysis, positive correlation was still found in embryonal rhabdomyosarcoma (ERMS, r = 0.214, p = 0.034) and alveolar rhabdomyosarcoma (ARMS, r = 0.498, p = 0.048). By focusing on the interaction of IGF pathway and p63, our results reveal additional signs to elucidate difference of pathogenesis and severity between ERMS and ARMS. Conclusions: The present study provides novel evidence to elucidate RMS pathogenesis and may be beneficial to clinical diagnosis and therapy for RMS. Highlights: Implications of IGF2, IGFBP2 and p63 in RMS were dettected in 114 specimens. Interaction of IGFBP2 and p63 might contribute to the pathogenesis of RMS. Connections of IGF2, IGFBP2 and p63 were detected in 114 specimens of pediatric RMS.